Preparing Students and Faculty to Engage in Interdisciplinary Research: Are We Up to the Challenge? - Tamera Keiter Humbert; Charla Lorenzen (Adult Education Research Conference, 2014)
The purpose of this paper is to highlight the strengths and challenges of a small, interdisciplinary research project between a foreign language department and an allied health professional program.